Image_13.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Once fully cooked, the bhakri is removed from the tava and served hot. It can be enjoyed plain or accompanied by chutney, pickle, curry, or vegetables. On average, a woman at the stall makes 45 to 50 bhakris in a day. Because the stall has no seating facility, customers pack the bhakri in newspapers and carry them home.